The Energy Conservation With A Ventilated Roof of Joglo’s House - Mohammad Pranoto Soedjarwo; Wiwik Dwi Susanti (Journal of Architectural Research and Design Studies, 2020)
The ventilation of buildings in hot and dry zones has to function differently from the warm and humid zones. When outside temperatures are rising higher than human body temperatures, cross ventilation through wide openings would not be useful; on the contrary, it would be a burden. To emphasize the sustainability of tropical homes, it is expected to maximize the use of the role of the roof opening in the building envelope in a passive manner. One passive cooling strategy is natural air. Circulation of natural ventilation in traditional Javanese built objects in humid tropical climates is used to achieve thermal comfort. Therefore, the problem that arises in this study is how far the Joglo-based roof element is in natural ventilation to form a comfortable space. This paper contains the elements of a Joglo-based house roof as a natural ventilation element. This study uses a computer simulation based on the program of CFD; the name is CFX-5, which is used to track the pattern and direction of air movement as well as the amount of air velocity and air direction in the Joglo-based roof ventilation object. The final value of these observations is between 0.389 to 0.489 m/s, which provides the majority cooling effect in the room, range between 0.489OC - 0.589OC. This was shown in the modified roof conditions, roof ventilation of the Joglo-Mangkurat-based roof is able to increase the speed of the air rate in the room.Keywords: energy conservation, ventilated roof, Joglo’s house.